COSMAN CITROEN (1881-1935), A MUNICIPAL ADVISORY AND INDEPENDENT ARCHITECT IN SURABAYA - Joko Triwinarto Santoso (Journal of Architecture&ENVIRONMENT, 2019)
A Dutch architect Cosman Citroen (1881-1935) is known as one of the well-known architects in the Netherlands Indies. In various articles or studies, he was known as the advisory architect of the Surabaya Municipality during his career. However, none of them was able to explain exactly since and until when he occupied the status and also when he underwent professional career as an independent architect. From this point, it can be drawn which works he produced during his service for the municipality and which ones created as an independent architect.